Haematological and biochemical reference intervals for three species of hydrophiine sea snakes (Hydrophis curtus, H. elegans and H. peronii) in Australia. Issue 3 (June 2015) - Gillett, Amber K.; Flint, Mark; Hulse, Lyndal; Hanger, Jon; Mills, Paul C.
Highlights: Haematological and biochemical reference intervals are provided for three species of Hydrophiine sea snakes. Reference intervals can be used to assess health in sea snakes. Lymph contamination is minimised by modifying blood collection methods. Most haematological and biochemical parameters are unaffected by lymph contamination. Graphical Abstract: Abstract: This study presents the first set of comprehensive reference intervals (RIs) for plasma biochemistry and haematology for three species of sea snakes common to the Indo-Pacific waters of Australia. In total 98 snakes, composed of Hydrophis curtus ( n   =  60), H.   elegans ( n  = 27) and H.   peronii ( n  = 11), were captured, clinically examined and had venous blood samples collected. All snakes were deemed healthy and in good to excellent body condition with snout to vent lengths of 40.7–73.9 cm ( H.   curtus ), 68.9–131.4 cm ( H.   elegans ) and 55.0–83.0 cm ( H.   peronii ), respectively. Lymphocyte numbers, alkaline phosphatase, alanine aminotransferase, creatine kinase and lactate dehydrogenase levels were species-dependent. All other parameters are presented as a single range for the three species. Gender ratio was evenly distributed for H.   curtus and H.   elegans, but 8/11 (73%) of H.   peronii were males. No significant differences were detected between males and females for any of the measured blood parameters. Lymph contamination was considered and accounted for. Although only three species of sea snakes are represented in this study, the RIs generated may be useful in the clinical assessment of other sea snake species.